Effects of waste glass powder as pozzolanic cement supplementary material for structural elements - Del Pino, Sebastian (2022)
The ever-growing global production of glass generates high waste percentages, the vast majority of which does not get recycled hence increasing the concern on its environmental impact. Studies on the pozzolanic properties of glass powder emerged as a solution to the abundance of waste glass powder available and its insufficient recycling. The aim of this study is to investigate the influence 10%,15% and 20% of waste soda-lime glass powder as partial cement replacement; fresh concrete tests were carried out, as well as compression strength tests at 28 days on grade 280 kg/cm2 concrete produced with pozzolanic cement. Tests results show an insignificant reduction of slump on the concrete mixes, an increase of air content and a decrease in density and compressive strength resistance with increasing glass powder substitution.